PENGEMBANGAN STRATEGI PEMBELAJARAN PAI YANG BERORIENTASI NILAI (AFEKTIF) - Asnah, Asnah (FORUM PAEDAGOGIK, 2016)
Through the development strategy of Islamic education study by orienting education assess, it is expected that it can develop the mental attitude, sensitive feeling (sympathy and empathy) and also it grows the awareness on believe in educated participant. Among these affective learning strategies are reflective strategy, transinternal and consideration. Reflective strategies by using rational and emotional approach, which give an opportunity to students to think and ponder at the same time the values, are contained in religious teachings delivered. While transinternal strategy, it emphasizes the internalization process with exemplary approach and habituation. Further consideration strategy is using a functional approach, in which students are asked to consideration of the attitude to be taken by providing various alternatives will be the consequences of the attitude to be taken.